Alarm bells ring in Vanuatu - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Since December 1998, three islands in Vanuatu have been infested by the red ant Wasmannia auropunctata. These tiny undesirables measure between just 1 and 1.5 mm, and build their nests in tree trunks or under waste vegetation, attacking plants - by...